TINJAUAN TENTANG PEMBELAJARAN PERMAINAN KASTI DALAM MEMBENTUK KARAKTER SISWA KELAS VA DI SEKOLAH DASAR INPRES OEBA 1 KOTA KUPANG - Manafe, Brian Ari Putra; Nafie, Agustinus; Rohi, Isak Riwu (Nusa Cendana University, 2021)
Seeing the reality of the student character who are increasingly losing moral wisdom and the decline in student character at this time. It is necessary to increase the quality in shaping student character to better. Through learning the game of baseball by instilling character values, children’s character can be well formed. The purpose of this study was to determine the learning of baseball games in shaping the student character of VA grade at SD Inpres Oeba 1 Kota Kupang. This research uses qualitative, while the primary data and secondary. Primary data are obtained from interviews, observations, questionnaires during the learning process, while secondary data comes from relevant notes or documents in the form of library data, books, journals, reports, photos related to research. Techniques of data collection used were: observation, questionnaires, interviews, and documentation. While the data analysis uses descriptive analysis. The findings of the researchers showed that learning the game of baseball in shaping student character of VA grade at SD Inpres Oeba 1 Kota Kupang by seeing students do the learning and role models of students in learning.